Institutional coordination arrangements as elements of policy design spaces: insights from climate policy - Lüpke, Heiner von; Leopold, Lucas; Tosun, Jale (Policy sciences, 2022)
This study offers insights into the institutional arrangements established to coordinate policies aiming at the mitigation of and adaptation to climate change. Drawing on the literature on policy design, we highlight institutional arrangements as elements of policy design spaces and contend that they fall into four categories that either stress the political or problem orientation of this activity: optimal, technical, political, and sub-optimal. We use original data on 44 major economies and greenhouse gas-emitting countries to test this expectation. These data capture various properties of national coordination arrangements, including the types of coordination instruments in place, the degree of hierarchy, the lead government agency responsible for coordination, and the scope of cross-sectoral policy coordination. The dataset also captures the degree to which non-state actors are involved in coordination and whether coordination processes are supported by scientific knowledge. Using cluster analysis, we show that the institutional arrangements for the horizontal coordination of climate policy do indeed fall into the four above-mentioned categories. The cluster analysis further reveals that a fifth, hybrid category exists. Interestingly, the political orientation dominates in the institutional arrangements for the horizontal coordination of climate change mitigation, whereas the problem orientation is more important in the arrangements for the horizontal coordination of climate change adaptation.
Gesehen am 23.01.2023